Two-dimensional reduced-physics model to describe historic morphodynamic behaviour of an estuary inlet - Harshinie Karunarathna (Marine Geology, 2016)
Understanding medium to long term morphodynamic change is important for sustainable coastal and estuary management. This paper analyses morphodynamic change of a complex estuary inletwhich is subjected tomultiple environmental drivers and proposes a reduced physics model to explain the historic medium term morphodynamic change of the inlet. The analysis shows that even though the estuary inlet undergoes multiscale morphological change, the changes that take place over a timescale of several years are more significant and important. The reduced physics model suggests that this simplified modelling approach is able to recognise principal historic morphodynamic trends in the estuary. However, the length and quality of the inlet bathymetry data set limits the applicability of the models and the quality of model outputs.